Alternative extrapolation-based symmetry boundary implementations for the axisymmetric lattice Boltzmann method - Zhang, Liangqi (2018)
In this study, alternative symmetry boundary implementations for the axisymmetric lattice Boltzmann (LB) method are proposed based on the nonequilibrium extrapolation and the direct extrapolation schemes. The proposed boundary schemes are directly implemented on the symmetry axis, and the postcollision distribution function and the macroscopic variables at the boundary nodes are extrapolated from the inner fluid nodes; thereby, the singularities arising at the symmetry axis (r = 0) during the collision and the macroscopic variable calculations are completely avoided. The accuracy of the present schemes is consistent with the well-established axisymmetric LB model. Moreover, in comparison with previous symmetry boundary schemes, the present implementations are slightly more accurate than the symmetry scheme by Guo et al. [Phys. Rev. E 79, 046708 (2009)] and numerically more stable than the specular reflection-based schemes.